De-risking private power in Bangladesh: How financing design can stop collusive contracting. (September 2022) - Khan, Mushtaq; Watkins, Mitchell; Zahan, Iffat
Abstract: Collusive contracting with private power plants in Bangladesh has resulted in high power prices that cost the taxpayer around U$1 billion in subsidies. The main driver of collusive contracting is the unwillingness of politically unconnected firms to engage in a high-risk environment. To attract investment, the government has adopted a targeted risk absorption strategy that negotiates mark-ups with interested firms. We argue that this strategy cannot discover the minimum mark-up that would induce investment. Moreover, because only politically connected investors are likely to be bidding and negotiating, this approach encourages investors to set high mark-ups. An alternative strategy is competitive risk-mitigation that provides contestable subsidies from development finance institutions (DFIs), such as preferential finance and partial risk guarantees. Contestable subsidies work by reducing risks of unconnected investors, encouraging their participation to make collusion more difficult, and constraining mark-ups. To test our hypothesis, we collect a dataset on plant-level DFI support and prices from 58 private power plants in Bangladesh from 2004 to 2017. Our empirical analysis finds that financing instruments with contestable subsidies from DFIs are associated with a 26% reduction in plant-level prices controlling for plant capacity, size, and fuel type. Highlights: Private power investors face high risks in places where contract enforcement is weak. Investors without political connections rarely participate allowing collusion. 'Contestable subsidies' accessible to all bidders increase participation. Participation enhances competitive scrutiny and constrains collusion. In Bangladesh over 2004–2017, contestable subsidies reduced power prices by 26%.